Design & Development of a DC Choke-Inductor or L Filter to Reduce the Harmonics during the Switching Process (Active Power Filters) - Ravi Rayappa; Manjunath, T. C. (Journal of Power Electronics and Devices, 2020)
In this paper, the Power Quality (PQ) improvement in integrated grid-connected power electronics-based systems using different types of active power filters is presented. In any integrated electrical power system/power electronic system, the harmonics caused by highly non-linear switching devices degrade the system's performance when switching of the linear or non-linear load takes place. Thus, harmonics is important to analyse in greater detail and we have to devise some algorithms/strategies towards its suppression, especially in the integrated power systems, and finally to safeguard the apparatus. In short, to say, the effect of harmonics plays a very important role in the successful operation of any equipment. If the harmonics are not taken care of properly, then it may lead to the output distortion & further adds to the reliability, the safety of the systems. Harmonic distortion is an undesirable effect for electrical, electronic & instrumentation based systems. With the increasing use of solid-state equipment, harmonic distortion in supply systems becomes more frequent and severe due to non-linear characteristics of such switching circuits. The experimental results show the efficacy of the methodology that is being developed by us. Filter design is developed in this research paper to counter-attack the harmonics & to make the supply smooth which occurs due to the switching on or off of the load. Hardware implementation of the work presented may be carried out using interfacing kits can & also can be thought of to validate the simulated work. Filter design is developed in this research paper to counter-attack the harmonics & to make the supply smooth which occurs due to the switching on or off of the load.